THE REVISED CONSORT STATEMENT FOR REPORTING RANDOMIZED TRIALS: EXPLANATION AND ELABORATION (2001) (PART II) - Douglas G. Altman; Kenneth F. Schulz; David Moher; Matthias Egger; Frank Davidoff; Diana Elbourne; Peter C. Getzsche; Thomas Lang; N. Chipigina (Рациональная фармакотерапия в кардиологии, 2016)
The Revised CONSORT Statement for Reporting Randomized Trials: Explanation and Elaboration (2001) (Part II).